2009
DOI: 10.1152/ajplung.00030.2008
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of mechanical ventilation and kidney health on lung function in an in vivo mouse model

Abstract: We hypothesized that the influence of acute kidney injury (AKI) on the sensitivity of the lung to an injurious process varies with the severity of the injurious process. Thus, we thought that AKI would exacerbate lung injury from low degrees of lung trauma but attenuate lung injury from higher degrees of lung trauma. C57BL/6 mice underwent AKI (30-min kidney ischemia) or sham surgery, followed at 24 h by 4 h of spontaneous breathing (SB), mechanical ventilation with low tidal volume (7 ml/kg, LTV), or mechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 39 publications
0
27
0
3
Order By: Relevance
“…More recently, Dodd-o et al [75] induced ischemic AKI (or sham) in mice and observed the effect of a variety of postprocedure ventilatory strategies on lung injury. In assessing the differences between mice who were permitted to spontaneously ventilate and those receiving mechanical ventilation with low and high tidal volumes (7 or 30 ml/kg), they controlled acid-base status by altering ventilatory dead space (preventing over ventilation), controlled volume status with appropriate fluid resuscitation, and selected appropriate fluids to minimize hyperchloremic metabolic acidosis.…”
Section: Animal Models Of Ali and Distant Organ Effectsmentioning
confidence: 99%
“…More recently, Dodd-o et al [75] induced ischemic AKI (or sham) in mice and observed the effect of a variety of postprocedure ventilatory strategies on lung injury. In assessing the differences between mice who were permitted to spontaneously ventilate and those receiving mechanical ventilation with low and high tidal volumes (7 or 30 ml/kg), they controlled acid-base status by altering ventilatory dead space (preventing over ventilation), controlled volume status with appropriate fluid resuscitation, and selected appropriate fluids to minimize hyperchloremic metabolic acidosis.…”
Section: Animal Models Of Ali and Distant Organ Effectsmentioning
confidence: 99%
“…Interestingly, in Dodd et al (14) the lung inflammation after moderate secondary injury (low tidal volume ventilation) was made more severe by antecedent AKI. Additionally, both of these experimental models analyzed result at time points significantly earlier than our model (Dodd: 4 h after 2nd hit and Zarbock: 2 h after 2nd hit) (14,47). Demonstration of impaired ventilatory mechanics and gas exchange would support a hypothesis that AKI leads to a functionally impaired lung after a direct secondary insult; however, with sublethality (no mortality up to 7 days), differences in murine lung mechanics can be subtle and difficult to elucidate.…”
Section: Discussionmentioning
confidence: 68%
“…In a subtotal nephrectomy model of AKI, a secondary ischemic insult resulted in increased lethality (42). In prior two-hit models involving AKI and lung injury, Dodd et al (14) showed that mice subjected to ischemic AKI had less pulmonary capillary leak after high tidal volume ventilation (30 ml/kg) than their sham cohorts (14). Similarly, Zarbock et al (47) highlighted a potential protective effect of uremic neutrophils in mice challenged with intratracheal hydrochloric acid.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidence suggests that ischemic AKI alters host immune reponse (107), blood-brain permeability and astrocyte function (108), and left ventricular systolic function (109). Experimental AKI leads to aberrant lung water balance and lung function (110)(111)(112). Clinical evidence indicates that patients with ARDS or ventilator-induced lung injury (VILI) with concurrent AKI have increased ventilator needs and duration (113).…”
Section: Impairment: Distal Targets Of Kidney Injurymentioning
confidence: 99%